Teacher Quality Dimensions in Improving the Quality of National Education at Madrasah Aliyah in Lampung - M. Ihsan Dacholfany; Agus Wibowo; Muhammad Kharis Fadillah (Jurnal Madania)
This article explores the development of teacher quality dimensions in improving the quality of national education. Methods This research uses a case study with a mixed methods approach. The sampling technique uses a random sampling technique with respondents. Based on the findings in this study, the results of the analysis were obtained with a Satorra-Bentler Scaled Chi-Square value of 189.190 and a p-value coefficient of 0.070 > 0.05, RMSEA of 0.030 <0.080, CFI ≥ 0.90, so the model obtained is "good fit" (acceptable model suitability) then the dimensions in the professional management of teachers in improving the quality of education are the three dimensions of learning which include lesson preparation, implementation, and evaluation. In addition, the results of the information obtained by students expect quality teachers such as having preparation, knowledge/ability in teaching, class management, personality, dedication, open-mindedness, responsibility, varied teaching methods, punctual work, and good judgment. This research suggests that if changes in the education system need to be developed, policy recommendations prioritize teacher staff and the determinants of teacher effectiveness.